Putative role of Bach1 gene in HbE/beta-thalassaemia patients - Lee, Tze Yan (2013)
Beta thalassaemia is an autosomal blood disorder due to a quantitative reduction or total absence of beta globin chain synthesis caused by beta globin gene mutations. Haemoglobin E/ beta thalassaemia individuals have a diverse clinical severity due to globin chain imbalance and the effects of other modifiers. Basic leucine zipper transcription factor 1 (Bach1) is known to be among the crucial molecules that has the ability to regulate gene expression when faced with oxidative stress. This study was done to investigate the role of Bach1 gene in HbE/ beta thalassaemia patients. Peripheral blood samples from 62 patients were collected. Full blood count analysis and HPLC were performed on the peripheral blood. Patients with blood transfusions of less than three months were excluded. A total of 47 selected samples without underlying iron deficiency or alpha thalassaemia co-inheritance were genotyped with ARMS PCR for common beta globin mutations and detection of uncommon beta globin mutations were done via direct gene sequencing. TaqMan® quantitative RT-PCR was employed to correlate Bach1 expression to severity, HO-1 and globin expression levels of HbE/ beta thalassaemia. Bach1 expression among 47 HbE/ beta thalassaemia patients varied up to 2-log differences which was positively correlated to age (p=0.006), alpha globin expression level (p=0.002), beta globin expression level (p=0.001), gamma globin expression level (p=0.001) and HO-1 expression level (p=0.001). Apart from that, Bach1 expression was also negatively correlated to reticulocytes level (p=0.005). The positive correlation of Bach1 expression with age could be due to the increasing oxidative stress caused by natural cellular ageing process. Excess precipitated alpha chains and unstable beta globin chains cause Bach1 expression to increase whereas Bach1 is correlated indirectly with gamma globin chains to ameliorate the clinical severity of HbE/ beta thalassaemia. The compensatory mechanism of Bach1 trying to counter-react with the increased reticulocyte counts and the indirect link of Bach1 with HO-1 as a cytoprotective vehicle further substantiate the role of Bach1 in modifying the phenotypic severity in HbE/ beta thalassaemia. Taken together, these results suggest that Bach1 could be a potential modifier of HbE/ beta thalasssaemia individuals.